Diversidad genética de germoplasma colombiano de zapallo (cucurbita moschata dúchesne exp. prior) (2004)
Se colectaron, caracterizaron morfológicamente y evaluaron agronómicamente 133 accesiones de Cucurbita moschata en Colombia (departamentos del Cauca, Valle del Cauca, Risaralda, Quindío, Caldas, Antioquia, Bolívar, Magdalena y Atlántico), las cuales presentaron alta diversidad en tamaño, forma y color de fruto. Los descriptores pubescencia de la hoja, color mancha de la hoja, días a floración masculina, días a floración femenina, espesor de pulpa, tamaño de semilla, forma de margen de semilla, ancho de fruto y peso promedio de fruto permitieron la diferenciación de grupos. Se encontró un índice de diversidad de 62% entre las accesiones colectadas en los departamentos de la región andina con las de la Costa Atlántica. Ninguno de los grupos presentó índices de similaridad del 100%. ABSTRACT This study was carried at Candelaria (Colombia), from August 2001 to July 2003. This study aimed at evaluating, by multivariate analyses techniques, the genetic diversity of 133 accesions, collected from distinct areas of regions of Colombia. The experimental design was of randomized complete blocks with four replications. The data (average) were collected from three plants per plot. Thirteen nine traits were evaluated, 9 vegetatives, 24 reproductives and 1 related to susceptibility to stress. The data were analysed using the herarquical method of WARD and were transformed into a complete disjunctive table, where the modalities of each character is a new variable. The analysis revealed five cluster, with to R2 = 97% and diversity index 62%. The most important characteristics to explain the variability were: days to first female and male flower, fruit width, fruit weight, flesh thickness, leaf pubescence dorsal and ventral surface, colour of leaf spots and seed size. The 5, 7, 47 , 109 and 28 accesion might be recommended for breeding programs. Keywords: Cucurbita moschata, Germplasm, Genetic resources, plant breeding, Morphology characterization.